Fishing kit implements from KHB-1: net sinkers and lures (poster) - Cavulli , Fabio; Scaruffi, Simona (Proceedings of the Seminar for Arabian Studies, 2011)
Several campaigns of excavation of the Middle Holocene coastal site of KHB-1 (Ra’s al-Khabbah, Sultanate of Oman) allowed the collection of numerous artefacts directly connected to fishing activities such as stone net sinkers, shell hooks, lures, and bone needles. They provide insights into the main subsistence strategy of the site. The poster paper focuses, in particular, on the c.400 stone net sinkers collected from the six phases of occupation recognized by the relevant archaeological deposits. The attested local production of these implements illustrates a careful choice of raw material in relation to the manufacturing technique used, indicating that a precise shape and weight were significant, and suggesting how morphological parameters might have been linked to a differentiation in fishing techniques and various species of prey found on the site. The collection has been organized into different groups following both morphological and dimensional trends (length, width, and weight), features that have their own functional (or cultural) implications. A complete study of the whole fishing kit will offer a basis for the understanding of fishing techniques that can be subsequently compared to the collected fish species, shedding new light on the complexity and advanced level of knowledge that these fishermen had of the sea in the Middle Holocene.